Efektivitas Program Posyandu Lansia di Kabupaten Sidoarjo - Agnes Tri Mahnolita; Lailul Mursyidah (Universitas Muhammadiyah Sidoarjo, 2018)
This research aims to know the effectiveness of Posyandu Lansia Program in Sidoarjo and to know the supporting and constraining factors in implementation of Posyandu Lansia Program. This descriptive qualitative research located in Sawotratap Village, Gedangan, Sidoarjo. This research focus on four of effectiveness indicators that is understanding of program, on time, on target, and in real change. The informants determination technique using purposive sampling that is the service officer of Lansia, midwife of the village, and elderly. The results showed that not all of elderly know the benefits and objectives of the Posyandu Program, the implementation schedule of Posyandu is not on time and often change. In terms of accuracy of the target already meet the health needs of the elderly and provide changes to improve the health of the elderly. The obstacles are the awareness of the elderly, the schedule changes and lack of maintenance the facilities so the elderly lazy to follow the activities. Meanwhile, the supporting factor is the funds from local budget to cover the needs of Posyandu activities, the number of officers is enough and assisted by the village midwife assistant